ANALISIS KEPUTUSAN PENGUSAHA MUSLIM DALAM MELAKUKAN PEMBIAYAAN PADA BANK SYARIâAH DI TULUNGAGUNG - Hidayati, Amalia Nuril (Dinamika, 2013)
ABTRACTThe establisment of bank muâamalah Indonesia is 1991is the triges of growing syariâah bank in Indonesia.Â Of course each syariah bank has interesting product to stimulate client, so it is important to be discussed about factors influenced customers to choose syariâah bank.Â The study aimed to analize knowledge factors, motivation, group concering and bank exceting towards moslem businessman choose syariâah bank in Tulungagung.Â The research finding stated that three factors, why moslem businessman choosed syariâah, namely; knowlwdge factors, motivation, and bank located.Kata Kunci: Analisis Keputusan, Pengusaha Muslim, Bank Syariâah.